Data on electroencephalographic activity while exposed to pink noise modified by the frequency responses of three headphone models - Norberto E. Naal-Ruiz (Elsevier, 2021)
The data described in this article refers to the experimental paradigm where subjects listened to the same pink noise modified by the frequency responses of three headphone models while their brain responses were recorded by means of electroencephalography. Six types of data are described: 1) pink noise sounds with a length of 2.73 s used for the experimental paradigm; 2) electrophysiological recordings, 29 in the first session and 25 in the last session recorded for five minutes; text files with 3) electrode positions and 4) information to identify physiological data and headphone group; 5) a table with technical specifications of the physical headphone model used in the experiment; and 6) a figure summarizing the experimental design. The information in this work can be used to compare the electrical activity of the brain in acoustic treatments where headphones are a key element to meet the therapeutic effect.